Young Women's Experiences of Self-harm: Commonalities, Distinctions and Complexities. (February 2016) - Curtis, Cate
Though self-harm is a significant problem among young people, the extant literature is somewhat unclear as to the meanings and functions of different forms. Nonetheless, it appears that young women engage in self-harm in general more frequently than any other group. This research explored the narratives of 22 young women who had engaged in both non-suicidal self-injury (NSSI) and suicidal behaviour, to examine the meanings of self-harm. The behaviours are distinct insofar as they take different forms and serve different purposes. However, a key contribution of this research is that, in contrast to constructions of self-harming behaviours as occurring on a continuum from the less to more severe with overlapping or confused motivations and intentions, the data suggest a cyclical pattern of behaviour, in which the protagonist moves between NSSI and suicidal behaviour, and NSSI is clearly counter-suicidal.